FOSTERING AWARENESS OF SELF IN THE EDUCATION OF SOCIAL WORK STUDENTS BY MEANS OF CRITICAL REFLECTIVITY - Ferreira, Sandra Berna; Ferreira, Regardt Jacobus (Social Work/Maatskaplike Werk, 2019)
Fostering awareness of self in the education of social work students has focused primarily on a micro-conceptualisation of the self, which implies that the attention was, and still is, mainly on the intrapsychic processes generated by theory and field practicum. But the development of the professional self should also encompass a macro-conceptualisation, where students have to ask themselves how they contribute to the maintenance of societal structures and how these structures influence them in the forming of their own assumptions and belief systems about the self and the world. Three categories of critical-reflectivity questions can be asked about a parable on death and dying, thereby sensitising students to the self as a product of, as well as a co-creator of, society in the grieving process. These questions furthermore resonate within an African-centred worldview in the understanding of the self.